Impact of hygiene of housing conditions on performance and health of two pig genetic lines divergent for residual feed intake. (27th June 2017) - Chatelet, A.; Gondret, F.; Merlot, E.; Gilbert, H.; Friggens, N. C.; Le Floc'h, N.
Abstract : Pigs selected for high performance may be more at risk of developing diseases. This study aimed to assess the health and performance of two pig lines divergently selected for residual feed intake (RFI) (low RFI (LRFI) v . high RFI (HRFI)) and housed in two contrasted hygiene conditions (poor v . good) using a 2×2 factorial design ( n =40/group). The challenge period (Period 1), started on week zero (W0) when 12-week-old pigs were transferred to good or poor housing conditions. At week 6 (W6), half of the pigs in each group were slaughtered. During a recovery period (Period 2) from W6 to W13 to W14, the remaining pigs ( n =20/group) were transferred in good hygiene conditions before being slaughtered. Blood was collected every three (Period 1) or 2 weeks (Period 2) to assess blood indicators of immune and inflammatory responses. Pulmonary lesions at slaughter and performance traits were evaluated. At W6, pneumonia prevalence was greater for pigs housed in poor than in good conditions (51% v . 8%, respectively, P <0.001). Irrespective of hygiene conditions, lung lesion scores were lower for LRFI pigs than for HRFI pigs ( P =0.03). At W3, LRFI in poor conditions had the highest number of blood granulocytes (hygiene×line, P =0.03) and at W6, HRFI pigs in poor conditions had the greatest plasma haptoglobin concentrations (hygiene×line, P =0.02). During Period 1, growth rate and growth-to-feed ratio were less affected by poor hygiene in LRFI pigs than in HRFI pigs (hygiene×line, P =0.001 and P =0.02, respectively). Low residual feed intake pigs in poor conditions ate more than the other groups (hygiene×line, P =0.002). Irrespective of the line, fasting plasma glucose concentrations were higher in poor conditions, whereas fasting free fatty acids concentrations were lower than in good conditions. At the end of Period 2, pneumonia prevalence was similar for both housing conditions (39% v . 38%, respectively). During Period 2, plasma protein concentrations were greater for pigs previously housed in poor than in good conditions during Period 1. Immune traits, gain-to-feed ratio, BW gain and feed consumption did not differ during Period 2. Nevertheless, at W12, BW of HRFI previously housed in poor conditions was 13.4 kg lower than BW of HRFI pigs ( P <0.001) previously housed in good conditions. In conclusion, health of the most feed efficient LRFI pigs was less impaired by poor hygiene conditions. This line was able to preserve its health, growth performance and its feed ingestion to a greater extent than the less efficient HRFI line.